Induction of steroid sulfatase expression by tumor necrosis factor-α through phosphatidylinositol 3-kinase/Akt signaling pathway in PC-3 human prostate cancer cells - Suh, Bo-Young (Korean Society for Biochemistry and Molecular Biology, 2011)
Steroid sulfatase (STS) is responsible for the hydrolysis of aryl and alkyl steroid sulfates and has a pivotal role in regulating the formation of biologically active estrogens. STS may be considered a new promising drug target for treating estrogen-mediated carcinogenesis. However, the molecular mechanism of STS expression is not well-known. To investigate whether tumor necrosis factor (TNF)-α is able to regulate gene transcription of STS, we studied the effect of TNF-α on STS expression in PC-3 human prostate cancer cells. RT-PCR and Western blot analysis showed that TNF-α significantly induced the expression of STS mRNA and protein in a concentration- and time-dependent manner. Treatment with TNF-α resulted in a strong increase in the phosphorylation of Akt on Ser-473 and when cells were treated with phosphatidylinositol (PI) 3-kinase inhibitors such as LY294002 or wortmannin, or Akt inhibitor (Akt inhibitor IV), induction of STS mRNA expression by TNF-α was significantly prevented. Moreover, activation of Akt1 by expressing the constitutively active form of Akt1 increased STS expression whereas dominant-negative Akt suppressed TNF-α-mediated STS induction. We also found that TNF-α is able to increase STS mRNA expression in other human cancer cells such as LNCaP, MDA-MB-231, and MCF-7 as well as PC-3 cells. Taken together, our results strongly suggest that PI 3-kinase/Akt activation mediates induction of human STS gene expression by TNF-α in human cancer cells.